2009
DOI: 10.1002/adfm.200800939
|View full text |Cite
|
Sign up to set email alerts
|

A General Approach to Semimetallic, Ultra‐High‐Resolution, Electron‐Beam Resists

Abstract: Commercial electron‐beam resists are modified into semimetallic resists by doping with 1–3 nm metal nanoparticles, which improve the resolution, contrast, strength, dry‐etching resistance, and other properties of the resist. With the modified resists, fine resist nanopatterns from electron‐beam lithography are readily converted into 5–50 nm, high‐quality multilayers for metallic nanosensors or nanopatterns via ion‐beam etching. This method solves the problem of the fabrication of fine (<50 nm) metallic nanodev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The need for directly patternable spin‐on hard masks that already possess the proper dry etching resistance with respect to silicon is thus increasing. Suitable modifications to improve the properties of high resolution electron‐beam (EB) resists have also been reported: chemical amplification (molecular structure or chemical composition modification) and doping with 1–3 nm metal nanoparticles of positive and negative tone resists (PMMA, ma‐N, ZEP) have been proposed: the former still presents the problems typical of organic resists, whereas the latter have a better dry etching resistance (generally in between the commercial resist and the metal used) but still lower than silicon …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for directly patternable spin‐on hard masks that already possess the proper dry etching resistance with respect to silicon is thus increasing. Suitable modifications to improve the properties of high resolution electron‐beam (EB) resists have also been reported: chemical amplification (molecular structure or chemical composition modification) and doping with 1–3 nm metal nanoparticles of positive and negative tone resists (PMMA, ma‐N, ZEP) have been proposed: the former still presents the problems typical of organic resists, whereas the latter have a better dry etching resistance (generally in between the commercial resist and the metal used) but still lower than silicon …”
Section: Methodsmentioning
confidence: 99%
“…Suitable modifi cations to improve the properties of high resolution electron-beam (EB) resists have also been reported: chemical amplifi cation (molecular structure or chemical composition modifi cation) and doping with 1-3 nm metal nanoparticles of positive and negative tone resists (PMMA, ma-N, ZEP) have been proposed: the former still presents the problems typical of organic resists, whereas the latter have a better dry etching resistance (generally in between the commercial resist and the metal used) but still lower than silicon. [ 15,16 ] In a previous contribution we reported a fi rst attempt to obtain a resist based on a hybrid organic-inorganic (HOI) system loaded to 80% with boehmite nanoparticles (Al 2 O 3 / AlO(OH). [17][18][19][20][21] Dry etching selectivity for silicon in excess of 60:1 (comparable to metallic masks under the same etching conditions) was obtained with this system in a set of tests involving deep X-ray lithography (XRL) and a fl uorine-based RIE-ICP etcher.…”
Section: Communicationmentioning
confidence: 99%
“…However, it is difficult to achieve a high aspect ratio for resist patterns in the sub-100 nm scale, in particular a size finer than 50 nm, with the use of current commercial electron beam (e-beam) resists [9,10]. This is attributed to the limited strength, etch resistance or large surface tension of the fine resist nanopatterns in developer solutions [11]. Although it has been reported that fine resist nanopatterns with a high aspect ratio could be achieved with methods such as mixing/doping of carbon nanotubes [12] or metal nanoparticles [11] into resists and using CO 2 gas to dry the developed resists [13], 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles leading to significant improvement in their mechanical properties. 164 The modified resist exhibited increased pattern collapse mitigation and enhanced etch resistance for pattern transfer using ion-beam etching. Con et al used coevaporation of Cr and polystyrene to incorporate metal into the polymeric matrix and reported stark improvement in the patterning contrast as well as dry etch resistance.…”
Section: Metal-containing Polymeric Resistsmentioning
confidence: 99%
“…reported doping commercial electron beam resists with bimetallic (PtFe, PtCo, etc.) nanoparticles leading to significant improvement in their mechanical properties 164 . The modified resist exhibited increased pattern collapse mitigation and enhanced etch resistance for pattern transfer using ion-beam etching.…”
Section: Metal-containing Resists In Electron Beam Lithography: An Ov...mentioning
confidence: 99%